NONSURGICAL RHINOPLASTY: SYSTEMATIC REVIEW - Nur Afiati, Shabrina; Wijaya, Natalia; Marini, Dini (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: The surge in demand for nonsurgical rhinoplasty, driven by patients seeking alternatives to the enduringly popular surgical rhinoplasty, emphasizes the need for skilled facial plastic surgeons proficient in filler placement. Offering nonsurgical rhinoplasty by experienced surgeons enhances safety, contributes to surgical practice success, and serves as a cost-effective, low-risk alternative, especially when patients are considering future surgery. Systematic reviews play a crucial role in consolidating evidence, informing practitioners about the latest developments, and establishing best practices in both nonsurgical and surgical rhinoplasty, contributing to improved patient care. Methods: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Results: Our search produced 22 results. After looking at the titles and summaries, we found 10  papers that fit our criteria. At first, we excluded several articles because they were written in review style and case reports. But after reading the full papers carefully, we included five papers in our final analysis. These papers included a retrospective analysis, observational study, and retrospective analysis of a prospective clinical registry. Conclusion: In conclusion, nonsurgical rhinoplasty, exemplified by a 14-year case series, is a highly gratifying and popular procedure, emphasizing an ascending technique for optimal outcomes. However, its potential complications necessitate experienced practitioners, urging caution and diligence. The systematic review supports the efficacy and safety of nonsurgical rhinoplasty using PDO sutures and fillers, especially in Asians, while emphasizing the importance of patient selection. Furthermore, the described "LG Nose Reshaping Technique" with hyaluronic acid proves safe and effective, warranting long-term studies, and the use of VYC-25L showcases high patient satisfaction and low adverse events when administered by skilled practitioners with optimized fillers.